2012
DOI: 10.4028/www.scientific.net/amr.488-489.335
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MgO Additive on Microstructure of Al<sub>2</sub>O<sub>3</sub>

Abstract: Abstract. In this work, the consolidation of different alumina particles via sintering process was conducted to the compacted alumina pellets. This consolidation was also assisted with the sintering aid, MgO to densify the final ceramic structure. Comparison between the influence of additive to the different particles size of compacted alumina by observing the microstructure and physical properties was conducted. The value physical properties and microstructure clearly show that for both particle size of alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 11 publications
(12 reference statements)
1
12
0
1
Order By: Relevance
“…In this pursuit of improving toughness, Al 2 O 3 based materials are often used as the benchmark due to its abundance, relative cheapness and excellent mechanical properties [9][10][11]. The introduction of the yttria stabilized zirconia (YSZ) toughening agent further increased the toughness of the zirconia toughened alumina (ZTA) ceramic composite [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this pursuit of improving toughness, Al 2 O 3 based materials are often used as the benchmark due to its abundance, relative cheapness and excellent mechanical properties [9][10][11]. The introduction of the yttria stabilized zirconia (YSZ) toughening agent further increased the toughness of the zirconia toughened alumina (ZTA) ceramic composite [12].…”
Section: Introductionmentioning
confidence: 99%
“…2 [2, 23]. The diffusion mechanism is commonly achieved near melting temperature of that particular ceramic in order to ensure the diffusion of loose particles to occurs [24]. The consolidation process of ceramic body during the firing stage in which bonding and growth of necks in between the particles binds the particles strongly that would increase the strength of the sintered body [2, 4].…”
Section: Advanced Materials Research Vol 795mentioning
confidence: 99%
“…12 Theoretically, increase in MW of PEG, the pore number as well as pore size in membranes will increase while also membranes with PEG at higher MW have higher permeation water flux (PWF) and higher hydraulic permeability due to higher porosity. [14][15][16] However, Arthanareeswaran et. al, reported that by increasing PEG MW enhance the viscosity in casting solution.…”
Section: 10 Introductionmentioning
confidence: 99%